Making Benefit Sharing Arrangements Work for Forest-dependent Communities : Insights for REDD+ Initiatives - PROFOR (World Bank, Washington, DC, 2013)
As donors pledge growing support for protecting and managing forests to address climate change, the question of how to pay tropical countries to reduce their emissions from deforestation and forest degradation assumes greater urgency. Depending on the detailed implementation of REDD plus at a national and international level, forest nations may be able to secure funding from a range of sources, including donors and multilateral funds (a funded approach) and the voluntary and compliance carbon markets (a carbon markets-based approach). These payments are supposed to act as financial incentives that will engender changes in behavior and policy frameworks, spur the development of appropriate institutional arrangements and needed technologies, and motivate both national and international coordination to achieve REDD plus objectives. These pages provide a brief synthesis of four papers financed by the Program on Forests (PROFOR). All four papers are included in a CD enclosed at the end of this booklet. The papers are: making benefit sharing arrangements work for forest-dependent people: overview of insights for REDD plus Initiative (Chandrasekharan Behr, 2012); identifying and working with beneficiaries when rights are unclear (Bruce, 2012); assessing options for effective mechanisms to share benefits (PwC, 2012); and benefit sharing in practice.